Late Follicular Phase Progesterone Elevation During Ovarian Stimulation Is Not Associated With Decreased Implantation of Chromosomally Screened Embryos in Thaw Cycles. Issue 10 (October 2020) - Hernandez-Nieto, Carlos; Lee, Joseph A.; Alkon-Meadows, Tamar; Luna-Rojas, Martha; Mukherjee, Tanmoy; Copperman, Alan B.; Sandler, Benjamin
Abstract : (Abstracted from Hum Reprod 2020;35:1889–1899) Although the physiologic mechanism remains unclear, late follicular phase progesterone elevation (LFPE) commonly occurs during controlled ovarian hyperstimulation (COH) for assisted-reproductive technology (ART) such as in vitro fertilization (IVF). Late follicular phase progesterone elevation has been associated with patient body mass index (BMI), ethnicity, ovarian reserve metrics, ovarian response to exogenous gonadotropins, number of follicles recruited during COH, dosage/duration of stimulation cycles, and other factors.